Metabolic syndrome and pre‐diabetes contribute to racial disparities in breast cancer outcomes: hypothesis and proposed pathways. Issue 7 (21st April 2016) - Gallagher, Emily J.; LeRoith, Derek; Franco, Rebeca; Antoniou, Irini Markella; Nayak, Anupma; Livaudais‐Toman, Jennifer; Bickell, Nina A.
Abstract: Background: Women with obesity and type 2 diabetes (T2D) are at greater risk of dying from breast cancer than women without these conditions. Obesity and T2D are associated with insulin resistance and endogenous hyperinsulinemia and are more common in Black women. There is increasing disparity in breast cancer mortality between Black and White women in the USA. We hypothesize that insulin resistance and endogenous hyperinsulinemia in Black women with breast cancer contribute to their greater breast cancer mortality and are associated with increased insulin receptor signalling in tumours. Methods: We will recruit 350 Black women and 936 White women with newly diagnosed breast cancer. We will determine the presence or absence of the metabolic syndrome/pre‐diabetes and insulin resistance by measuring body mass index, waist circumference, lipids, blood pressure, glucose, insulin‐like growth factor binding protein 1 and insulin. Breast cancer prognosis will be determined by a Nottingham Prognostic Index (NPI), with poor prognosis being defined as NPI >4.4. Tumour insulin receptor signalling will be determined by immunohistochemistry. Insulin receptor subtype expression will be measured using Nanostring. Analysis of these factors will determine whether endogenous hyperinsulinemia is associated with a worse prognosis in Black women than White women and increased tumour insulin receptor signalling. Conclusions: The results of this study will determine if the metabolic syndrome and pre‐diabetes contribute to racial disparities in breast cancer mortality. It may provide the basis for targeting systemic insulin resistance and/or tumour insulin receptor signalling to reduce racial disparities in breast cancer mortality. Copyright © 2016 John Wiley & Sons, Ltd.